Optimal setting of PV and battery energy storage in radial distribution systems using multi‐objective criteria with fuzzy logic decision‐making. Issue 1 (25th November 2020) - Selim, Ali; Kamel, Salah; Jurado, Francisco; Lopes, Joao A. Peças; Matos, Manuel
Abstract: Minimising the total power losses and enhancing the voltage profile is achieved using a proposed multi‐objective chaotic salp swarm algorithm with fuzzy logic decision‐making. The proposed multi‐objective chaotic salp swarm algorithm is utilised to determine the optimal size and location of photovoltaic in radial distribution system to minimise the total power losses, total voltage deviation, and maximise the voltage stability index. In addition, the proposed multi‐objective chaotic salp swarm algorithm is used to find suitable scheduling for battery energy storage charge/discharge during 24 h considering the intermittent nature of photovoltaic power generation. The proposed algorithm is tested on standard and practical radial distribution systems (IEEE 33‐bus and 94‐bus Portuguese systems). The performance of the proposed algorithm is validated by comparing its results with those obtained by other competitive optimisation techniques. The obtained results prove the ability of the proposed algorithm to achieve an efficient setting for photovoltaics and battery energy storages and determine their optimal allocations in order to minimise the power losses and enhance the voltage profile with satisfying all operating constraints.